Abortion Lawfare in Mexico's Supreme Court: Between the Right to Health and Subnational Autonomy - Rachel Sieder; Yacotzin Bravo Espinosa (Revista Direito GV)
Abstract This article addresses Mexico's contentious politics of abortion, legal frames, and the role of the Supreme Court. In Mexico's federal system, subnational legislatures have been the principal site of abortion lawfare, with initiatives passed to both decriminalize and restrict access to abortion, pitting frames of women's rights to health against the fetal “right to life from the moment of conception.” In this article we offer a detailed mapping of critical junctures in Mexico's abortion lawfare since 2007, based on a review of draft decisions, public transcripts, and final rulings of the Supreme Court. We suggest that while the Court has appeared largely reactive to different legislative initiatives and legal challenges, failing to produce definitive rulings affirming women's universal right to abortion, its assertion of federal authority and its increasingly restricted reading of the scope of states’ policy-making powers has in practice favored the arguments put forward by the pro-choice movement, reaffirming and even expanding women's sexual and reproductive rights. We highlight a key area for future comparative inquiry on sexual and reproductive rights lawfare in Latin America: the interplay between supreme courts and subnational legislatures in federal systems, and the ways that this shapes movement and counter-movement framings and strategies.